Preparation and characterization of polymer microcapsules containing ammonium persulfate with controlled burst release. (21st August 2019) - Zuo, Mingming; Zhang, Qifan; Mei, Haibo; Zhang, Jie; Zuo, Xiaobing; Geng, Fei
Abstract: Microcapsules containing water-soluble ammonium persulfate (APS) cores as gel breakers that offer controlled burst release, are become increasingly important in improving the gel breaking efficiency of fracturing fluids in oil fields. To date, microcapsules with various control slow release behaviors have been thoroughly investigated, but microcapsules with burst release properties are rarely studied. Here, we reported a novel inverse emulsion polymerization method to exploit this new type of microcapsule. The microcapsules were composed of APS cores and stimuli-responsive P(MMA- co -AA) copolymer shells. The microcapsules have spherical structures with diameters of 10 to 16 μ m. The encapsulated cores offer controlled burst release from the microcapsules and their beginning time of burst release could be delayed up to 42 h. Moreover, all of the cores could be completely released within 1 h from the microcapsules. The temperature, pH, and salt concentration change could stimulate the release. These novel microcapsules might have promising applications in oil exploration, batteries, monomer polymerization, fiber printing, and grease.